1994
DOI: 10.1063/1.466467
|View full text |Cite
|
Sign up to set email alerts
|

Quantum scattering studies of long-lived resonances for the reaction Ne+H+2→NeH++H

Abstract: Theoretical studies of the reactivity and spectroscopy of H+CO=HCO. I. Stabilization and scattering studies of resonances for J=0 on the Harding a b i n i t i o surfaceThe bending-corrected rotating linear model (BCRLM) is used to investigate the reaction of neon with Hi (v=0-3) using three different fits to the ab initio potential-energy surface computed by Urban, Jaquet, and Staemmler. Numerous long-liy~d scattering resonances are found for each surface. The number and position of these scattering resonances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 51 publications
(2 reference statements)
1
33
0
Order By: Relevance
“…Also, resonance structures in the cumulative reaction probability have been found for other barrierless reactions such as H ϩO 2 , 47-50 HeϩH 2 ϩ , 51 and NeϩH 2 ϩ . 52,53 B. O" 1 D…¿D 2 Figure 5 shows the calculated total reaction probabilities for the O( 1 D)ϩD 2 (vϭ0,jϭ0,1, and 2)→ODϩD reaction as a function of the total energy. Despite that there exists a large difference in mass, the behavior of the calculated total reaction probabilities is essentially the same as that of O( 1 D)ϩH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, resonance structures in the cumulative reaction probability have been found for other barrierless reactions such as H ϩO 2 , 47-50 HeϩH 2 ϩ , 51 and NeϩH 2 ϩ . 52,53 B. O" 1 D…¿D 2 Figure 5 shows the calculated total reaction probabilities for the O( 1 D)ϩD 2 (vϭ0,jϭ0,1, and 2)→ODϩD reaction as a function of the total energy. Despite that there exists a large difference in mass, the behavior of the calculated total reaction probabilities is essentially the same as that of O( 1 D)ϩH 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of scattering calculations one would think that this might be a small error of 0.006 eV, which is better than the accuracy of the fit. BCRLM reaction probabilities [426] for the three fits show, however, that the average height of the strongly oscillating reaction probability Pg--+ o varies between 0.05 (Fit 1) and 0.15 (Fit 3). ..…”
Section: Comparison Of Different Fits In Some Test Casesmentioning
confidence: 94%
“…Detailed information of the three different fits and the minimum energy paths is given in [125]. The differences in the fits are seen more clearly when these PESs are used in dynamics calculations: bound state calculations for the rovibrational levels of NeHt and its isotopomeres, quantum scattering studies of long lived resonances for the reaction Ne + Ht ~ NeH+ + H [426] and quasiclassical and approximate quantum mechanical (R-IOSA) studies of the intramolecular isotope effects in proton transfer: Ne + HD+ ~ NeH+ (NeD+) + D (H) [427].…”
Section: Comparison Of Different Fits In Some Test Casesmentioning
confidence: 99%
“…In 1993, an accurate PES of the ground state of the NeH þ 2 reactive system was presented by Pendergast et al [1] using the coupled-electron approach, whereafter more studies have been conducted based on this PES. Kress et al [2] reported the state-tostate reaction probabilities for zero total angular momentum based on the bending-corrected rotating linear model using quantumdynamics calculations. State-selected integral cross sections as a function of energy using the coupled-states approximation were reported by Gilibert and co-workers [3,4].…”
Section: Introductionmentioning
confidence: 99%